ENTROPIC APPROACH TO ASSESSING THE PROJECT MANAGEMENT PROCESSES QUALITY - Обронова, Алеся (SWorldJournal, 2022)
Introduction. Quality management is one of the areas of knowledge in project management and implies two components - the quality of the product and the project management processes quality. Since the success of a project is the achievement of the project'